The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1002/jlb.3ma0522-273rr
|View full text |Cite
|
Sign up to set email alerts
|

Morphine disrupts macrophage functions even during HIV infection

Abstract: HIV‐associated neurocognitive impairment (HIV‐NCI) is a debilitating comorbidity that reduces quality of life in 15–40% of people with HIV (PWH) taking antiretroviral therapy (ART). Opioid use has been shown to increase neurocognitive deficits in PWH. Monocyte‐derived macrophages (MDMs) harbor HIV in the CNS even in PWH on ART. We hypothesized that morphine (MOR), a metabolite of heroin, further dysregulates functional processes in MDMs to increase neuropathogenesis. We found that, in uninfected and HIV‐infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…DRG cultures were prepared from whole DRGs not cleared of non-neuronal cells. While it has been reported that these cells express MOR and can act indirectly to contribute to sensitization of DRG neurons 44 , 45 by an activated of immune response, in vivo 46 48 However, we prepared low-density DRG neuronal cultures that were used within 3 days, at which time there is minimal growth of non-neuronal cells and nociceptor neurites. This approach has allowed us to patch nociceptors without neighboring non-neuronal cells within > 100 µm.…”
Section: Discussionmentioning
confidence: 99%
“…DRG cultures were prepared from whole DRGs not cleared of non-neuronal cells. While it has been reported that these cells express MOR and can act indirectly to contribute to sensitization of DRG neurons 44 , 45 by an activated of immune response, in vivo 46 48 However, we prepared low-density DRG neuronal cultures that were used within 3 days, at which time there is minimal growth of non-neuronal cells and nociceptor neurites. This approach has allowed us to patch nociceptors without neighboring non-neuronal cells within > 100 µm.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have found that the use of opioids (e.g., morphine, fentanyl) causes, in addition to some common side effects such as tolerance, addiction, respiratory depression, nausea, and constipation, an immunosuppressive effect that increases the risk of infection [ 1 , 2 ]. It is known that opioid addicts are at increased risk of infection, and the intersection between HIV infection and intravenous drug abuse has been identified [ 3 , 4 ]. In vitro and in vivo experiments, as well as epidemiological and clinical studies on different patient populations, have also shown that opioids such as morphine and fentanyl impair the function of macrophages, natural killer (NK) cells, and T cells, and weaken the intestinal barrier, inducing immunosuppression of the innate and adaptive immune systems, as well as damaging the mucosal barrier [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%